Erik Cainberg ja hänen reliefisarjansa Turun vanhassa akatemiatalossa - Pöykkö, Kaarina (1991)
Erik Cainberg (1771-1816) descended, on his mother's side, from the Rijfs, the well-known family of church builders, with whom he worked for a few years at an early age. In 1790 he was enrolled as a student at the Royal Academy of Arts in Stockholm; he studied under J.T. Sergel, the sculptor, and was trained in the neoclassical tradition. At the end of his studies he received a grant to study in Rome, where he stayed from 1802 to the end of 1810. After his return to Stockholm Cainberg experienced a great deal of difficulty in gaining his livelihood but he survived the hardships by assisting his old master in the most strenuous sculpturing assignments. In 1813 he was offered a stucco project at Turku, Finland, his old homeland, which, in 1809, had become an autonomous Grand Duchy under the rule of Russia. At Turku the construction of a new main building for the Academy of Turku (the University) had been going on since 1802. By 1813 construction had reached the stage where it was time to undertake the decoration of the main hall. In addition to stucco, the original decorating plans also included a series of six reliefs. When Cainberg arrived in the spring to start working on the stucco project, the plans were changed, and he was given the assignment to make the series of reliefs. The programme for the series of reliefs had been adopted by the Senate of the Academy as early as 1807. It drew upon the romantic and nationalistic principles of the era and was titled 'The Progression of Enlightenment and Sciences in Finland'. The motifs of the reliefs were as follows: (1) pagan culture – Väinämöinen playing; (2) the advent of Christianity in Finland; (3) the Reformation; (4) the establishment of the Academy of Turku; (5) the era of Gustav the Third; and (6) the laying of the foundation stone of the new academy building in 1802. The motifs were derived from the Swedish period of Finnish history: by 1813, however, the political situation had undergone a change, and the Senate of the Academy came to the conclusion that the new situation should also be reflected in the series of reliefs. The programme was redesigned: the era of Gustav the Third was omitted, and its place was taken by the relief representing the laying of the foundation stone. The new motif of the last relief was to represent the new period in Finnish history; it was Alexander the First's visit to the Academy of Turku in 1809. The series of plaster reliefs in the Turku academy building remained Cainberg's main work. The remainder consists of four relief portraits made of plaster and a number of anonymous decorative sculptures in churches built by the Rijfs. The original idea of the series of reliefs was based on a chronological presentation of rulers. The series was supposed to start from the door on the left with 'Pagan Culture', with Väinämöinen as the central figure, and with 'The Advent of Christianity' under King Eric in the 12th century on the opposite wall. The first two were followed on the left-hand side by King Gustav Vasa as the Reformer, and on the right-hand side by Queen Christina as the Founder of the Academy. The place nearest the cathedra on the left was reserved for the era of Gustav the Third and that on the right for the laying of the foundation stone of the academy building during King Gustav the Fourth Adolf' s reign. The narrative was supposed to culminate in a colossal bust of Gustav the Fourth Adolf in an apse behind the cathedra. The overall design presupposed a symmetrical alternation of exterior and interior scenes. This symmetrical arrangement was broken in the new, implemented plan for the reliefs, whereas the chronology of the rulers was preserved culminating in a colossal bust of Alexander the First behind the cathedra commissioned from the Russian sculptor Ivan Martos. There are a number of interesting details in the analyses of the reliefs. 'Pagan Culture' is important since it is the first representation of Väinämöinen; it is based on the book Mythologia Fennica by Christfrid Ganander. The figure of Väinämöinen bears features of Greek portraits and Michelangelo's Moses. The figure of the Wnter Fairy brings Berini's fountains to the mind; the models for The figure of the bards and the bear can be found in the engravings included in the works by Skjöldebrand and Acerbi. The major problem in the relief representing the advent of Christianity in Finland is the location of the most important figures: the bishop takes a modest position on the left, and the central position is given to a monk. The threatening figure on the extreme right can be interpreted as that of Lalli, who killed the bishop. The figure of King Eric resembles the statue of Gustav the Third by Sergel. The figures in the Reformation relief are easy to interpret: the centre is occupied by Gustav Vasa, to whom Mikael Agricola is showing his translations into Finnish; behind him there is a young male assistant. The person supporting himself on the rostrum is Prince John, and on the left two youngsters can be seen having a look at a broken statue of a saint. In the fourth relief Queen Christina is signing the foundation charter of the Academy of Turku. This is a typical full-length female portrait as found in neoclassical sculpture. The figure of Axel Oxenstierna standing next to her can be seen to incorporate features of the figures to be found in the pedestal of the equestrian statue of King Gustav the Second Adolf by Sergel. The portrait of King Gustav the Second Adolf in the background resembles the portraits of the hero king produced by Sergel. The relief representing the laying of the foundation stone is a reportage picture of a kind. The gallery of personages in the relief can be identified. The way in which the layout has been designed is atypical of Cainberg, but it is obvious that he has received the idea from C.C. Gjörwell, the architect of the academy building. The central figure of the last relief is Alexander the First, to whom Queen Christina is introducing the muse of the river Aura. Alexander is represented as Apollo, and Christina as Pallas Athene, for both of whom models can be found in the antique collection of Gustav the Third. The muse of the river Aura seems to be a personification of Finland. Erik Cainberg's art bears a strong imprint of Sergel's influence. In addition, the period that he spent in Rome was important. The neoclassical style of Canova and Thorvaldsen had a marked impact on the artistic expression that was adopted by Cainberg in Stockholm.